The pursuit of development :economic growth ,social change and ideas - Goldin, Ian (Oxford University Press, 2016)
What do we mean by development? How can citizens, governments and the international community foster development? The process by which nations escape poverty and achieve economic and social progress has been the subject of extensive examination for hundreds of years. The notion of development itself has evolved from an original preoccupation with incomes and economic growth to a much broader understanding of development. In his new book, Ian Goldin considers the contributions that education, health, gender, equity and other dimensions of human well-being make to development, and discusses why it is also necessary to take into account the role of institutions and the rule of law as well as sustainability and environmental concerns. -- Provided by publisher.